2020
DOI: 10.3390/electronics9040690
|View full text |Cite
|
Sign up to set email alerts
|

Use of Both Eyes-Open and Eyes-Closed Resting States May Yield a More Robust Predictor of Motor Imagery BCI Performance

Abstract: Motor-imagery brain-computer interface (MI-BCI) is a technique that manipulates external machines using brain activities, and is highly useful to amyotrophic lateral sclerosis patients who cannot move their limbs. However, it is reported that approximately 15–30% of users cannot modulate their brain signals, which results in the inability to operate motor imagery BCI systems. Thus, advance prediction of BCI performance has drawn researchers’ attention, and some predictors have been proposed using the alpha ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In this study, the results of correlation analysis indicate that alpha band RP over SMA from a few seconds before MI was positively correlated with the BCI performance (see Figure 4). Similar results were obtained in previous studies (Ahn et al, 2013;Kwon et al, 2020). In addition, the alpha-band RP from the resting state was proposed before as an index of tracking cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the results of correlation analysis indicate that alpha band RP over SMA from a few seconds before MI was positively correlated with the BCI performance (see Figure 4). Similar results were obtained in previous studies (Ahn et al, 2013;Kwon et al, 2020). In addition, the alpha-band RP from the resting state was proposed before as an index of tracking cognitive function.…”
Section: Discussionsupporting
confidence: 89%
“…The crucial relationship with MI-BCI performance was not found using band power and questionnaires. Some studies have reported that SMR such as mu rhythms in the resting-state is related to MI performance ( Blankertz et al, 2010 ; Kwon et al, 2020 ). In fact, this argument seems plausible because alpha and beta power are decreased during the MI and used as typical features of the MI paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to anticipate the evoked MI responses, several pre-training electrophysiological indicators are reported, like functional connectivity of resting-state networks [ 20 ], rhythm activity of eyes-open and eyes-closed resting-states [ 21 ], pre-cue EEG rhythms over different brain regions [ 22 ], and the power spectral density estimates of resting wakefulness (before the cue-onset of the conventional MI trial timing and resting state) [ 23 , 24 ]. Although this last predictor is one of the most used, its curve-fitting method depends heavily on various parameters that are difficult to determine, regardless of the resting data employed [ 25 ]. Other predictors are derived from measuring the change in electrophysiological properties across the training sessions [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%